Effect of Music Therapy Combined with Rehabilitation Training on Reducing the Fall Risk in Elderly Patients with Multimorbidity - CHEN Xiaoya; YU Nannan; DING Jiajia; GUO Shanshan; DONG Hongsheng; DING Yuqing; ZHONG Na (康复学报)
ObjectiveTo explore the effect of music therapy combined with rehabilitation training on reducing the fall risk in elderly patients with multimorbidity.MethodsA total of 72 elderly patients with chronic multimorbidity hospitalized in the Department of Rehabilitation Medicine of Shanghai Jiahua Hospital from October 2021 to October 2022 were selected. The subjects were randomly assigned to the treatment group and the control group, with 36 cases in each group. In the course of the study, there was one case of urinary system infection, one case discharged for home care, and one case where the evaluation could not be completed in the control group, and one case died of pulmonary infection in the treatment group. Finally, 33 cases were included in the control group and 35 cases in the treatment group. The control group received low intensity aerobic training (30 min a time, once a day, five times per week) and dynamic and static balance training (20 min a time, once a day, five times per week) for a total of 12 weeks. In addition to the treatment plan of the control group, the treatment group received music therapy (30 min a time, once a day, five times per week) for 12 weeks. Berg balance scale (BBS) was used to evaluate balance function, 10-meter walking test (10MWT) was use to to assess walking speed, average electromyography (AEMG) and integrated electromyography (iEMG) values of tibialis anterior muscle were collected to evaluate muscle function before and after 12 weeks of intervention, and adverse events were recorded.ResultsCompared with those before treatment, the EMG values (AEMG and iEMG) of bilateral tibialis anterior muscle in both groups were significantly higher (P<0.05). Compared with the control group, the EMG values (AEMG and iEMG) of bilateral tibialis anterior muscle in the treatment group were significantly higher (P<0.05). The BBS score of both groups were significantly higher than those before treatment (P<0.05). However, when compared to the control group, the treatment group did not show a significant increase in BBS score, and the difference was not statistically significant (P>0.05). Compared with that before treatment, the result of the 10MWT in the treatment group increased significantly (P<0.05). Compared with the control group, the 10MWT result of the treatment group was significantly better (P<0.05). No adverse events were recorded indicating a high level of safety.ConclusionMusic therapy combined with rehabilitation training can better improve the lower limb muscle function and walking speed of elderly patients with multimorbidity, and can improve the balance function to some extent. The overall fall prevention effect is better than rehabilitation training alone.